A novel F420‐dependent anti‐oxidant mechanism protects Mycobacterium tuberculosis against oxidative stress and bactericidal agents. Issue 4 (28th December 2012) - Gurumurthy, Meera; Rao, Martin; Mukherjee, Tathagata; Rao, Srinivasa P. S.; Boshoff, Helena I.; Dick, Thomas; Barry, Clifton E.; Manjunatha, Ujjini H.
Summary Mycobacterium tuberculosis (Mtb) is an aerobic bacterium that persists intracellularly in host macrophages and has evolved diverse mechanisms to combat and survive oxidative stress. Here we show a novel F420‐dependent anti‐oxidant mechanism that protects Mtb against oxidative stress. Inactivation of the fbiC gene in Mtb results in a cofactor F420‐deficient mutant that is hypersensitive to oxidative stress and exhibits a reduction in NADH/NAD+ ratios upon treatment with menadione. In agreement with the recent hypothesis on oxidative stress being an important component of the pathway resulting in cell death by bactericidal agents, F420− mutants are hypersensitive to mycobactericidal agents such as isoniazid, moxifloxacin and clofazimine that elevate oxidative stress. The Mtb deazaflavin‐dependent nitroreductase (Ddn) and its two homologues Rv1261c and Rv1558 encode for an F420H2‐dependent quinone reductase (Fqr) function leading to dihydroquinones. We hypothesize that Fqr proteins catalyse an F420H2‐specific obligate two‐electron reduction of endogenous quinones, thereby competing with the one‐electron reduction pathway and preventing the formation of harmful cytotoxic semiquinones, thus protecting mycobacteria against oxidative stress and bactericidal agents. These findings open up an avenue for the inhibition of the F420 biosynthesis pathway or Fqr‐class proteins as a mechanism to potentiate the action of bactericidal agents.